LELANG EKSEKUSI HAK TANGGUNGAN PADA PT. PERMODALAN NASIONAL MADANI CABANG PADANG PASCA HOLDING MELALUI KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) PADANG - Yulia Vitria Yohannes, Dwikornida , (Fakultas Hukum Universitas Tamansiswa Padang, 2022)
Auction is the sale of goods open to the public with written and/or oral price bids that increase or decrease to reach the highest price, which is preceded by an Auction Announcement. Regulations for every financial institution, both bank and non-bank, including PT. Madani National Capital or PNM, in general when the debtor is in default and has been categorized as a non-performing loan, the creditor can carry out the process of submitting an auction related to collateral tied to mortgage rights through the Padang State Property and Auction Service Office (KPKNL). The Mortgage Execution Auction Process carried out by PNM Post Holding must carry out the process of changing the name of the Persero's status on the Mortgage Certificate. The process of carrying out the auction is regulated based on the Vendu Regulation (Stbl.Tahun 1908 No.189 amended by Stbl.1940 No.56) which in regulation refers to the technical implementation of the auction and Regulation of the Minister of Finance of the Republic of Indonesia Number: 213/PMK.06/2020, dated 22 December 2020 concerning Instructions for Conducting Auctions. The results of this study are that the Auction Implementation Process is regulated in the Regulation of the Minister of Finance of the Republic of Indonesia Number 213/PMK.06/2020, December 22 2020 concerning Instructions for Conducting Auctions, PNM in submitting a collateral auction must change the name of the company by removing the phrase